Lateral Change Detection of Ghezlozan River Channel from 1993 to 2013 - fariba Esfandiary Darabad; Masoud Rahimi; khodadad lotfy; ebadi elhameh (تحقیقات کاربردی علوم جغرافیایی)
So that the morphological and transverse changes of the Ghezelozan River have been evident in recent years and caused some problems. In this study, the detection of river side changes was carried out using satellite imagery of TM and OLI Landsat 5 and 8 in the period 1993 to 2013, during which an interval of 158 km from the Ghezelozan River, using the transect method evaluated. The channel duct was divided into 24 transects based on morphology and the process of change. The average migration rate of the Gezelozan River duct has been around 4.47 m / year over the past 20 years. The highest transhumance rate between 1993 and 2013, at 10.58 m / year, is related to transect 16, resulting in 52.51 hectares on the right bank of the river. Overall, the results show that during the period 1993 to 2013, close to 207.14 hectares was added to the right bank of the river and nearly 215.31 hectares from the right bank were decreased. Also, in this study, sinusoidal index was used to study the shape of the duct flat, based on which there are 15 sinusoidal transects.